High-strength steel plate and method of manufacturing the same

KR103018282B1Active Publication Date: 2026-09-11JFE STEEL CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020247021021
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-14
Filing Date
2022-12-06
Publication Date
2026-09-11
Estimated Expiration
2042-12-06

Smart Images

  • Figure 112024068112031-PCT00001
    Figure 112024068112031-PCT00001
  • Figure 112024068112031-PCT00002
    Figure 112024068112031-PCT00002
  • Figure 112024068112031-PCT00003
    Figure 112024068112031-PCT00003
Patent Text Reader

Abstract

The present invention provides a high-strength steel sheet having a tensile strength of 1320 MPa or higher and excellent ductility, hole expandability, and delayed fracture resistance. The high-strength steel sheet has a specific compositional composition, wherein the amount of diffusible hydrogen in the steel is 0.50 mass ppm or less, tempered martensite and bainite is 70.0% or more, fresh martensite is 15.0% or less, and the iron-based carbides present in the tempered martensite and bainite have an average equivalent radius of 0.10 μm or less, an average aspect ratio of 4.5 or less, and the ratio (p) of tempered martensite and bainite containing iron-based carbides oriented in the same direction within the range of 0 to 10° of the major axis is 25 to 70%.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a high-strength steel plate and a method for manufacturing the same. Background Technology

[0002] Recently, from the perspective of global environmental conservation, there is a growing demand to lighten vehicle bodies to improve fuel efficiency.

[0003] At this time, the vehicle body is made lighter while maintaining the strength of the vehicle body. For example, conventionally, high-strength steel plates with a tensile strength (TS) of 980 MPa or higher are used (Patent Document 1). Prior art literature

[0004] International Publication No. 2020 / 045219 The problem to be solved

[0005] Recently, it has been desired to use high-strength steel plates with a tensile strength (TS) of 1320 MPa or higher for frame parts around the cabin of the vehicle body.

[0006] However, as the strength of steel sheets increases, their formability may become insufficient, making it difficult to press-process them into complex shapes. One indicator of formability is hole expandability, which is evaluated by a hole expansion test.

[0007] In addition, for parts obtained by cold pressing, for example, high-strength steel sheets with a tensile strength of 1320 MPa or higher, there is a risk of delayed fracture.

[0008] Delayed fracture is a phenomenon in which, when a stressed component is placed in a hydrogen intrusion environment, hydrogen penetrates into it, causing a decrease in interatomic bonding strength or local deformation, thereby causing microcracks to form and the component to be destroyed as the microcracks propagate.

[0009] For this reason, high-strength steel plates require good resistance to delayed fracture in addition to sufficient hole expansion.

[0010] The present invention is made in consideration of the above points and aims to provide a high-strength steel plate having a tensile strength of 1320 MPa or more, and excellent hole expandability and delayed fracture resistance. means of solving the problem

[0011] The inventors, after careful consideration, discovered that the above objective is achieved by adopting the following configuration, and thus completed the present invention.

[0012] That is, the present invention provides the following [1] to [7].

[0013] [1] A steel having a composition in mass% of C: 0.130 to 0.350%, Si: 0.50 to 2.50%, Mn: 2.00 to 4.00%, P: 0.100% or less, S: 0.0500% or less, Al: 0.001 to 2.000%, N: 0.0100% or less, with the remainder being Fe and unavoidable impurities, and a microstructure having a diffusible hydrogen content in the steel of 0.50 mass ppm or less, and in the microstructure, the total area ratio of tempered martensite and bainite is 70.0% or more, and the area ratio of fresh martensite is 15.0% or less, and the iron-based carbides present in the tempered martensite and bainite have an average equivalent radius of 0.10 7 to 35 iron-based carbides / µm, having an average aspect ratio of 4.5 or less and, among the tempered martensite and bainite, where the major axis direction is aligned in the same direction within the range of 0 to 10°. 2 A high-strength steel plate having a ratio (p) of tempered martensite and bainite containing as a number density of 25 to 70%.

[0014] [2] The above composition of components is further composed of, in mass%, Ti: 0.100% or less, Nb: 0.100% or less, V: 0.500% or less, W: 0.500% or less, B: 0.0100% or less, Ni: 2.000% or less, Co: 2.000% or less, Cr: 1.000% or less, Mo: 1.000% or less, Cu: 1.000% or less, Sn: 0.500% or less, Sb: 0.500% or less, Ta: 0.100% or less, Zr: 0.200% or less, Hf: 0.020% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0100% or less. A high-strength steel plate described in [1] above, containing at least one selected element.

[0015] [3] High-strength steel sheet described in [1] or [2] above, having a plating layer on the surface.

[0016] [4] The high-strength steel sheet described in [3] above, in which the plating layer is an alloy plating layer.

[0017] [5] A method for manufacturing a high-strength steel sheet as described in [1] or [2] above, wherein a steel slab having the compositional composition described in [1] or [2] above is heated to 1100°C or higher and hot-rolled at a finishing rolling end temperature of 850 to 950°C to obtain a hot-rolled steel sheet, the hot-rolled steel sheet is coiled at a coiling temperature of 700°C or lower and subsequently cold-rolled to obtain a cold-rolled steel sheet, and heat treatment is performed on the cold-rolled steel sheet, wherein in the heat treatment, the cold-rolled steel sheet is maintained at a temperature range T1 of 800 to 950°C for 30 seconds or more, then cooled to a cooling stop temperature T2 of 250°C or lower, then heated to a temperature range T3 of 250 to 400°C at a heating rate of 6.0 to 14.0°C / s and then cooled for 30 seconds or more A method for manufacturing a high-strength steel sheet, wherein, in the above cooling, the cold-rolled steel sheet is first cooled to a temperature T at an average cooling rate R1 of 10.0 to 50.0 ℃ / s under conditions satisfying the following Equations 1 and 2, and then secondarily cooled to a cooling stop temperature T2 at an average cooling rate R2.

[0018] Equation 1 : 0.10 < (R2 / R1) < 0.70

[0019] Equation 2: (21.52×T+5630)×R2 -0.022 ≥ 12200

[0020] [6] A method for manufacturing a high-strength steel sheet as described in [5], wherein, after the heat treatment, a plating treatment is performed on the cold-rolled steel sheet to form a plating layer.

[0021] [7] A method for manufacturing a high-strength steel sheet as described in [6], wherein the plating treatment described above includes an alloying plating treatment that alloys the plating layer. Effects of the invention

[0022] According to the present invention, a high-strength steel plate having a tensile strength of 1320 MPa or more and excellent hole expandability and delayed fracture resistance can be provided. Specific details for implementing the invention

[0023] [High-strength steel plate]

[0024] The high-strength steel plate of the present invention has the component composition and microstructure described below, and also satisfies the amount of diffusible hydrogen in the steel described below.

[0025] Hereinafter, "high-strength steel plate" will also be simply referred to as "steel plate."

[0026] The thickness of the steel plate is not particularly limited, but, for example, 0.3 to 3.0 mm, and 0.5 to 2.8 mm is preferred.

[0027] High strength means that the tensile strength (TS) is 1320 MPa or higher.

[0028] The high-strength steel sheet of the present invention has a tensile strength of 1320 MPa or more, and also has excellent hole expansion and delayed fracture resistance characteristics. For this reason, the high-strength steel sheet of the present invention has great utility value in industrial fields such as automobiles and electrical equipment, and is particularly useful for lightweighting the frame parts of automobile bodies.

[0029] <Composition>

[0030] The composition of the high-strength steel plate of the present invention (hereinafter also referred to as the “composition of the composition of the present invention for convenience”) will be explained.

[0031] In the component composition of the present invention, “%” means “mass%” unless specifically stated otherwise.

[0032] 《C: 0.130 % to 0.350 %》

[0033] C increases the strength of tempered martensite, bainite, and fresh martensite.

[0034] In addition, C precipitates fine carbides that serve as hydrogen trap sites within tempered martensite and bainite, thereby improving delayed fracture resistance.

[0035] To obtain these effects sufficiently, the amount of C is 0.130% or more, preferably 0.150% or more, and more preferably 0.170% or more.

[0036] On the other hand, if the C content is excessively high, the strength of the steel plate becomes excessively high, which increases the steel's susceptibility to hydrogen embrittlement, making it impossible to obtain sufficient delayed fracture resistance. In addition, weldability, which is important when joining automotive parts, deteriorates.

[0037] For this reason, the amount of C is 0.350% or less, preferably 0.330% or less, and more preferably 0.310% or less.

[0038] 《Si: 0.50% to 2.50%》

[0039] Si inhibits the excessive formation and growth of carbides. Because of this, when reheating during the heat treatment described later, the carbides (iron-based carbides) formed tend to align in the same direction, thereby improving the resistance to delayed fracture. In addition, the decrease in hole expandability caused by the difference in hardness between the carbides and each microstructure is suppressed.

[0040] In order to obtain these effects, the amount of Si is 0.50% or more, preferably 0.55% or more, and more preferably 0.60% or more.

[0041] On the other hand, if the amount of Si is excessive, the steel sheet becomes embrittled, making it difficult to obtain good hole expansion.

[0042] For this reason, the Si content is 2.50% or less, preferably 2.30% or less, and more preferably 2.00% or less.

[0043] 《Mn: 2.00% to 4.00%》

[0044] Mn forms a microstructure consisting mainly of tempered martensite and bainite, thereby suppressing the hardness difference between the structures and improving hole expandability. If the amount of Mn is insufficient, soft phases such as ferrite are formed, and a hardness difference that cannot be ignored occurs between the structures, so sufficient hole expandability is not obtained.

[0045] For this reason, the amount of Mn is 2.00% or more, preferably 2.20% or more, and more preferably 2.50% or more.

[0046] On the other hand, if the amount of Mn is excessive, the steel plate becomes embrittled, making it difficult to obtain good hole expansion.

[0047] For this reason, the amount of Mn is 4.00% or less, preferably 3.70% or less, and more preferably 3.50% or less.

[0048] 《P : 0.100 % or less》

[0049] P embrittles the steel plate through grain boundary segregation, which has an adverse effect on delayed fracture resistance and weldability. For this reason, the amount of P is 0.100% or less, preferably 0.080% or less, more preferably 0.070% or less, even more preferably 0.030% or less, and particularly preferably 0.010% or less.

[0050] 《S : 0.0500 % or less》

[0051] S segregates at grain boundaries and embrittles the steel sheet during hot working. In addition, S forms sulfides, which adversely affects the resistance to delayed fracture. For this reason, the amount of S is 0.0500% or less, preferably 0.0400% or less, more preferably 0.0300% or less, even more preferably 0.0100% or less, and particularly preferably 0.0050% or less.

[0052] 《Al: 0.001 ~ 2.000%》

[0053] Al reduces inclusions in the steel sheet by acting as a deoxidizer. For this reason, the amount of Al is 0.001% or more, preferably 0.005% or more, more preferably 0.010% or more, and even more preferably 0.015% or more.

[0054] On the other hand, if the amount of Al is excessive, the risk of cracking in the steel slab increases when casting the steel slab, thereby reducing manufacturability. For this reason, the amount of Al is 2.000% or less, preferably 1.500% or less, more preferably 1.000% or less, even more preferably 0.500% or less, and particularly preferably 0.100% or less.

[0055] 《N : 0.0100 % or less》

[0056] N has an adverse effect on delayed fracture resistance due to the formation of nitrides. If the amount of N is excessive, coarse nitrides are formed, and the deterioration of delayed fracture resistance becomes significant. For this reason, it is desirable for the amount of N to be as low as possible. Specifically, the amount of N is 0.0100% or less, preferably 0.0080% or less, and more preferably 0.0070% or less.

[0057] Other Elements

[0058] The composition of the present invention may additionally contain, in mass%, at least one element selected from the group consisting of the elements listed below.

[0059] (Ti : 0.100 % or less, Nb : 0.100 % or less, V : 0.500 % or less)

[0060] Ti, Nb, and V contribute to precipitation strengthening, so they are effective for increasing the strength of steel sheets. In addition, Ti, Nb, and V refine the austenite grain size, or consequently refine tempered martensite and bainite, or form fine precipitates that serve as hydrogen trap sites, thereby improving the delayed fracture resistance.

[0061] On the other hand, if Ti, Nb, and V are excessively high, when heating the steel slab during hot rolling, Ti, Nb, and V remain undissolved, leading to an increase in coarse precipitates and potentially deteriorating the resistance to delayed fracture.

[0062] For this reason, the amount of Ti and the amount of Nb are each preferably 0.100% or less, more preferably 0.080% or less, and even more preferably 0.050% or less. The amount of V is preferably 0.500% or less, more preferably 0.450% or less, and even more preferably 0.400% or less.

[0063] Although the lower limit is not specifically limited, from the perspective of obtaining the effect of adding these elements, the amount of Ti, the amount of Nb, and the amount of V are each preferably 0.001% or more, more preferably 0.003% or more, and even more preferably 0.005% or more.

[0064] (W : 0.500 % or less)

[0065] W improves the quenching properties of the steel sheet. In addition, W improves delayed fracture resistance by generating fine carbides containing W that serve as hydrogen trap sites, or by refining tempered martensite and bainite.

[0066] However, if W is excessively high, when heating the steel slab during hot rolling, coarse precipitates such as WN or WS that remain undissolved increase, and the resistance to delayed fracture deteriorates. For this reason, the amount of W is preferably 0.500% or less, more preferably 0.300% or less, and even more preferably 0.150% or less.

[0067] The lower limit of the amount of W is not specifically limited, but from the perspective of obtaining the effect of adding W, for example, 0.010% and 0.050% is preferred.

[0068] (B: 0.0100% or less)

[0069] B is effective for improving quenching properties. In addition, B forms a microstructure consisting mainly of tempered martensite and bainite, thereby preventing a decrease in hole expansion properties.

[0070] However, if B is excessively high, moldability may be reduced. For this reason, the amount of B is preferably 0.0100% or less, more preferably 0.0070% or less, and even more preferably 0.0050% or less.

[0071] The lower limit of the amount of B is not specifically limited, but from the perspective of obtaining the effect of adding B, for example, 0.0005% and 0.0010% is preferred.

[0072] (Ni : 2.000 % or less)

[0073] Ni increases the strength of the lecture through employment reinforcement.

[0074] However, if the amount of Ni is excessively high, the area ratio of fresh martensite becomes excessive, and the pore expandability is reduced. For this reason, the amount of Ni is preferably 2.000% or less, more preferably 1.000% or less, and even more preferably 0.500% or less.

[0075] The lower limit of the Ni amount is not specifically limited, but from the perspective of obtaining the effect of adding Ni, for example, 0.010% and 0.050% is preferred.

[0076] (Co : 2.000 % or less)

[0077] Co is an element effective for improving quenchability and is effective for strengthening steel sheets.

[0078] However, if Co is excessively high, it causes deterioration in moldability. For this reason, the amount of Co is preferably 2.000% or less, more preferably 1.000% or less, and even more preferably 0.500% or less.

[0079] The lower limit of the amount of Co is not specifically limited, but from the perspective of obtaining the effect of adding Co, for example, 0.010% and 0.050% is preferred.

[0080] (Cr : 1.000 % or less)

[0081] Cr improves the balance of strength and ductility.

[0082] However, if the Cr content is excessive, the cementite dissolution rate is delayed when reheating during the heat treatment described later, and relatively coarse carbides with Fe as the main component, such as cementite, remain undissolved, causing the delayed fracture resistance to deteriorate. For this reason, the Cr content is preferably 1.000% or less, more preferably 0.800% or less, and even more preferably 0.500% or less.

[0083] The lower limit of the Cr amount is not specifically limited, but from the perspective of obtaining the effect of adding Cr, for example, 0.030% and 0.050% is preferred.

[0084] (Mo: 1.000 % or less)

[0085] Mo improves the balance of strength and ductility. In addition, Mo improves delayed fracture resistance by producing fine carbides containing Mo that serve as hydrogen trap sites, or by refining tempered martensite and bainite.

[0086] However, if the amount of Mo is excessive, the chemical treatment performance deteriorates significantly. For this reason, the amount of Mo is preferably 1.000% or less, more preferably 0.800% or less, and even more preferably 0.500% or less.

[0087] The lower limit of the amount of Mo is not specifically limited, but from the perspective of obtaining the effect of adding Mo, for example, 0.010% and 0.050% is preferred.

[0088] (Cu : 1.000 % or less)

[0089] Cu is an element effective for strengthening steel. In addition, because Cu inhibits hydrogen from penetrating the steel sheet, it has superior resistance to delayed fracture.

[0090] However, if the amount of Cu is excessive, the area ratio of fresh martensite becomes excessive, and the pore expandability deteriorates. For this reason, the amount of Cu is preferably 1.000% or less, more preferably 0.500% or less, and even more preferably 0.200% or less.

[0091] The lower limit of the amount of Cu is not specifically limited, but from the perspective of obtaining the effect of adding Cu, for example, 0.010% and 0.050% is preferred.

[0092] (Sn: 0.500% or less, Sb: 0.500% or less)

[0093] Sn and Sb suppress decarburization of the surface layer region of the steel plate (a region with a depth of several tens of μm from the surface of the steel plate) caused by nitriding or oxidation of the surface of the steel plate, thereby preventing a decrease in the area ratio of tempered martensite on the surface of the steel plate.

[0094] However, if these elements are excessively abundant, it leads to a decrease in toughness. For this reason, the amount of Sn and the amount of Sb are each preferably 0.500% or less, more preferably 0.100% or less, and even more preferably 0.050% or less.

[0095] The lower limits of the Sn amount and Sb amount are not specifically limited, but from the perspective of obtaining the effect of adding Sn and Sb, for example, 0.001% and 0.003% are preferred, respectively.

[0096] (Ta : 0.100 % or less)

[0097] Ta contributes to high strength by forming alloy carbides or alloy carbonitrides. In addition, Ta is partially dissolved in Nb carbides or Nb carbonitrides to form complex precipitates such as (Nb,Ta) (C,N), thereby significantly suppressing the coarsening of precipitates and stabilizing the contribution to strength by precipitation strengthening.

[0098] However, even if Ta is added in excess, not only are these effects saturated, but costs also increase. For this reason, the amount of Ta is preferably 0.100% or less, more preferably 0.080% or less, and even more preferably 0.070% or less.

[0099] The lower limit of the amount of Ta is not specifically limited, but from the perspective of obtaining the effect of adding Ta, for example, 0.005% and 0.010% is preferred.

[0100] (Zr : 0.200 % or less)

[0101] Zr improves the quenchability of the steel sheet. In addition, Zr improves delayed fracture resistance by generating fine carbides containing Zr that serve as hydrogen trap sites, or by refining tempered martensite and bainite.

[0102] However, if Zr is excessively high, it causes an increase in inclusions, etc., and causes defects on the surface and inside of the steel sheet, thereby deteriorating the delayed fracture resistance. For this reason, the Zr content is preferably 0.200% or less, more preferably 0.150% or less, and even more preferably 0.100% or less.

[0103] The lower limit of the Zr amount is not specifically limited, but from the perspective of obtaining the effect of adding Zr, for example, 0.005% and 0.010% is preferred.

[0104] (Hf : 0.020 % or less)

[0105] Hf affects the distribution state of oxides, making the delayed breakdown characteristics better.

[0106] However, if Hf is excessively high, it degrades the formability of the steel sheet. For this reason, the Hf content is preferably 0.020% or less, more preferably 0.015% or less, and even more preferably 0.010% or less.

[0107] The lower limit of the Hf amount is not specifically limited, but from the perspective of obtaining the effect of adding Hf, for example, 0.001% and 0.003% is preferred.

[0108] (Ca : 0.0100 % or less, Mg : 0.0100 % or less, REM : 0.0100 % or less)

[0109] Ca, Mg, and REM (rare earth metals) spheroidize the shape of sulfides, thereby improving the adverse effect of sulfides on hole expansion.

[0110] However, if these elements are excessively abundant, they cause an increase in inclusions, etc., and cause defects on the surface and inside of the steel sheet, thereby deteriorating the delayed fracture resistance. For this reason, the Ca content, Mg content, and REM content are each preferably 0.0090% or less, more preferably 0.0080% or less, and even more preferably 0.0070% or less.

[0111] The lower limits of the Ca, Mg, and REM amounts are not specifically limited, but from the perspective of obtaining the effect of adding Ca, Mg, and REM, for example, 0.0005% and 0.0010% are preferred, respectively.

[0112] Residue: Fe and inevitable impurities

[0113] The remainder of the composition of the components of the present invention consists of Fe and unavoidable impurities.

[0114] <Microtissue>

[0115] Next, the microstructure of the high-strength steel plate of the present invention (hereinafter also referred to as the “microstructure of the present invention for convenience”) will be described.

[0116] In order to obtain the effects of the present invention, satisfying only the component composition of the present invention described above is insufficient, and it is necessary to satisfy the microstructure of the present invention described below.

[0117] The area ratio below is the area ratio for the entire microtissue. The area ratio of each tissue is determined by the method described in the [Examples] below.

[0118] Area ratio of total tempered martensite and bainite: 70.0% or more

[0119] Tempered martensite and bainite contribute to tensile strength.

[0120] In addition, using tempered martensite and bainite as the main materials is effective for increasing hole expandability while maintaining high strength.

[0121] To obtain these effects sufficiently, the total area ratio of bainite and tempered martensite is 70.0% or more, preferably 72.0% or more, and more preferably 74.0% or more.

[0122] Meanwhile, although the upper limit is not specifically limited, considering the manufacturing conditions, the total area ratio of tempered martensite and bainite is preferably 95.0% or less, more preferably 93.0% or less, and even more preferably 90.0% or less.

[0123] Area ratio of fresh martensite: 15.0% or less

[0124] Fresh martensite creates a large difference in hardness between tempered martensite and bainite, and thus reduces hole expandability during punching due to this difference in hardness. For this reason, it is necessary to avoid having an excess of fresh martensite in the steel sheet.

[0125] Specifically, in terms of obtaining good hole expandability, the area ratio of fresh martensite is 15.0% or less, preferably 14.0% or less, and more preferably 13.0% or less.

[0126] Remnant Organization

[0127] Examples of the microstructure excluding tempered martensite, bainite, and fresh martensite (residual microstructure) include retained austenite, ferrite, pearlite, etc. For the reason that it does not impede the effects of the present invention, the area percentage of the residual microstructure in the microstructure of the present invention is preferably 15.0% or less.

[0128] Iron Carbide

[0129] Next, iron carbides are explained.

[0130] Iron carbides exist in tempered martensite and bainite.

[0131] Iron carbides are carbides composed mainly of Fe and C, such as cementite (θ carbide), ε carbide, and χ carbide, and mainly refer to cementite.

[0132] Some of the Fe contained in iron carbides may be substituted with other elements such as Mn, Si, and Cr.

[0133] (Average equivalent radius: 0.10 µm or less)

[0134] If the average equivalent radius of the iron carbides is excessively large, the iron carbides become excessively coarse; consequently, voids originating from the iron carbides are prone to occur during press processing, leading to a deterioration in hole expandability.

[0135] For this reason, the average equivalent radius of the iron carbide is 0.10 μm or less, preferably 0.08 μm or less, and more preferably 0.06 μm or less.

[0136] (Average aspect ratio: 4.5 or less)

[0137] If the average aspect ratio of iron carbides is excessively large, stress is concentrated during press processing, making it easy for voids caused by cracking of iron carbides to occur, particularly in the shear section, and thus good hole expandability cannot be obtained.

[0138] For this reason, the average aspect ratio of iron carbides is 4.5 or less, preferably 4.3 or less, and more preferably 4.5 or less.

[0139] The average radius of the circle and the average aspect ratio of the iron carbide are obtained by the method described in the [Example] below.

[0140] 《Ratio (p): 25 ∼ 70 %》

[0141] Next, among tempered martensite and bainite, iron-based carbides with the major axis oriented in the same direction within the range of 0 to 10° are 7 to 35 pieces / µm 2 Explain the ratio (p) of tempered martensite and bainite included in the number density (for convenience, also simply referred to as "ratio (p)").

[0142] As described above, iron carbides exist in tempered martensite and bainite.

[0143] First, regardless of whether iron carbides are present or not, the total area occupied by grains of tempered martensite and bainite in the microstructure is denoted as, for example, area SA1.

[0144] Next, among the particles containing iron-based carbides (tempered martensite and bainite), attention is paid to particles that appropriately contain iron-based carbides with uniform orientation. More specifically, 7 to 35 iron-based carbides / µm with the major axis oriented in the same direction within the range of 0 to 10°. 2 Focus on the particles included in the number density, and let the area occupied by those particles be, for example, area SA2.

[0145] The ratio (p) (unit: %) is the ratio of area SA2 to area SA1 (=100×SA2 / SA1).

[0146] By having a ratio (p) greater than a certain value, the delayed fracture characteristics can be improved without impairing hole expandability.

[0147] Typically, coarse iron carbides present at lath boundaries and / or block boundaries become a source of voids during deformation. However, since uniformly oriented iron carbides are fine and do not elongate extremely, they have a small adverse effect on hole expansion.

[0148] In addition, a structure in which the orientation of iron carbides is unified tends to have a larger number of iron carbides compared to a structure in which it is not, and by including such a structure in a steel sheet, the number of hydrogen trap sites can be increased, thereby improving the resistance to delayed fracture.

[0149] Therefore, the value of the ratio (p) is 25% or more, 26% or more is preferable, 29% or more is more preferable, 30% or more is even more preferable, 35% or more is particularly preferable, and 39% or more is most preferable.

[0150] On the other hand, if a steel sheet contains an excessive amount of a structure in which the orientation of iron carbides is unified, the likelihood of voids originating from cementite forming increases during processing, which adversely affects hole expansion.

[0151] For this reason, in terms of obtaining good hole expandability, the value of the ratio (p) is 70% or less, 65% or less is preferable, and 60% or less is more preferable.

[0152] The ratio (p) is obtained by the method described in the [Example] below.

[0153] <Diffusible hydrogen content in steel: 0.50 mass ppm or less>

[0154] From the perspective of securing good delayed fracture resistance characteristics, the diffusible hydrogen content in the steel is 0.50 mass ppm or less, preferably 0.40 mass ppm or less, and more preferably 0.30 mass ppm or less.

[0155] The lower limit of the diffusible hydrogen content in the steel is not specifically limited, but due to production technology constraints, for example, it is 0.01 mass ppm.

[0156] The amount of diffusible hydrogen in the steel is determined by the method described in the [Example] below.

[0157] <Plating Layer>

[0158] The high-strength steel sheet of the present invention may have a plating layer on its surface. The plating layer is formed by a plating treatment described later.

[0159] Examples of plating layers include zinc plating layers (Zn plating layers) and Al plating layers, among which zinc plating layers are preferred. The zinc plating layer may contain elements such as Al and Mg. The plating layer may be an alloyed plating layer (alloyed plating layer).

[0160] The plating layer adhesion amount (amount per side) is 20 g / m² from the perspective of plating layer adhesion amount control and corrosion resistance. 2 The above is desirable, and 25 g / m² 2 The above is more desirable, and 30 g / m² 2 The above is more desirable.

[0161] Meanwhile, in terms of adhesion, the deposition amount of the plating layer is 120 g / m² 2 The following is preferable, and 100 g / m² 2 The following is more preferable, and 70 g / m² 2 The following is more desirable.

[0162] [Method for manufacturing high-strength steel plates]

[0163] Next, a method for manufacturing a high-strength steel plate according to the present invention (hereinafter also referred to as the "manufacturing method of the present invention" for convenience) will be described.

[0164] <Steel Slab>

[0165] In the manufacturing method of the present invention, first, a steel slab (steel material) having the component composition of the present invention described above is prepared.

[0166] Steel slabs are cast from molten steel by known methods, such as continuous casting, for example.

[0167] The method for manufacturing molten steel is not particularly limited, and known methods using converters, electric furnaces, etc., may be adopted.

[0168] Hot Rolling

[0169] In the manufacturing method of the present invention, a prepared steel slab is hot-rolled under the conditions described below (heating temperature and finish rolling end temperature) to obtain a hot-rolled steel sheet.

[0170] Heating temperature: 1100 ℃ or higher

[0171] In hot rolling, the steel slab is heated.

[0172] Precipitates present during the heating stage of the steel slab exist as coarse precipitates in the finally obtained steel plate, and not only do not contribute to strength but also adversely affect the resistance to delayed fracture.

[0173] The presence of coarse precipitates inhibits the formation of iron carbides, so after the heat treatment described later, the ratio (p) becomes too low, and the resistance to delayed fracture deteriorates.

[0174] For this reason, coarse precipitates formed during the casting of steel slabs need to be redissolved as much as possible. If the heating temperature of the steel slab is excessively low, redissolution becomes insufficient, resulting in inferior strength or resistance to delayed fracture.

[0175] Therefore, the heating temperature of the steel slab is 1100 ℃ or higher, and preferably 1150 ℃ or higher.

[0176] From the perspective of reducing rolling load and from the perspective of smoothing the surface of the steel plate obtained by scaling off surface defects (bubbles, segregation, etc.) of the steel slab, it is desirable that the heating temperature of the steel slab be within the above range.

[0177] The upper limit of the heating temperature of the steel slab is not specifically limited, but if it is excessively high, scale loss increases along with an increase in the amount of oxidation. For this reason, the heating temperature of the steel slab is preferably 1400°C or lower, and more preferably 1350°C or lower.

[0178] Finishing rolling end temperature: 850 ~ 950 ℃

[0179] The steel slab heated to the heating temperature described above undergoes hot rolling, including finish rolling, to become a hot-rolled steel sheet.

[0180] If the finishing rolling end temperature is excessively low, an excess of ferrite or pearlite is generated in the microstructure of the hot-rolled steel sheet, and in the microstructure after the heat treatment described later, the total area ratio of tempered martensite and bainite is reduced, resulting in a decrease in strength (tensile strength). In addition, the rolling load increases, and the rolling load becomes larger.

[0181] For this reason, the finishing rolling end temperature is 850 ℃ or higher, preferably 855 ℃ or higher, and more preferably 860 ℃ or higher.

[0182] Meanwhile, if the finishing rolling end temperature is excessively high, the excessive growth of precipitates present during the heating stage of the steel slab and the formation of new coarse precipitates are promoted. Since the presence of coarse precipitates inhibits the formation of iron carbides, the ratio (p) becomes too low after the heat treatment described later, and the resistance to delayed fracture deteriorates.

[0183] In addition, the amount of oxide (scale) generated increases rapidly, and the surface quality tends to deteriorate after the pickling and cold rolling described later.

[0184] In addition, if scale cannot be sufficiently removed by pickling, it has a negative effect on hole expansion.

[0185] In addition, the crystal grain size may become excessively coarse, causing surface roughness during press processing.

[0186] For this reason, the finishing rolling end temperature is 950 ℃ or lower, preferably 940 ℃ or lower, and more preferably 930 ℃ or lower.

[0187] <Gwonchwi>

[0188] The hot-rolled steel sheet obtained by hot rolling is wound at the wound temperature described below.

[0189] Rolling temperature: 700 ℃ or lower

[0190] If the coiling temperature is excessively high, an excess of ferrite or pearlite is generated in the microstructure of the hot-rolled steel sheet, and in the microstructure after the heat treatment described later, the total area ratio of tempered martensite and bainite becomes insufficient, which may cause a decrease in strength (tensile strength). In addition, an oxide film that is difficult to remove by pickling is formed on the surface of the hot-rolled steel sheet, which not only damages the surface appearance after cold rolling but may also cause a deterioration in hole expansion ability.

[0191] For this reason, the winding temperature T is 700 ℃ or lower, preferably 680 ℃ or lower, and more preferably 670 ℃ or lower.

[0192] Meanwhile, although the coiling temperature may be low, from the perspective of productivity, 400°C or higher is preferable, 420°C or higher is more preferable, and 430°C or higher is even more preferable. If the coiling temperature is within this range, it is easy to reduce the rolling load during cold rolling and also easy to achieve a good shape of the cold-rolled steel sheet obtained by cold rolling.

[0193] For coiled hot-rolled steel sheets (coils), pickling may be performed if necessary prior to the cold rolling described below. The pickling method may follow conventional methods. Skin pass rolling may be performed to correct the shape and improve pickling performance.

[0194] <Cold Rolling>

[0195] The coiled hot-rolled steel sheet is pickled as needed, then cold-rolled to become a cold-rolled steel sheet.

[0196] The reduction rate in cold rolling is preferably 25% or more, and more preferably 30% or more.

[0197] Meanwhile, excessive reduction leads to an excessive rolling weight, causing an increase in the load on the mill used for cold rolling. For this reason, a reduction rate of 75% or less is desirable, and 70% or less is more desirable.

[0198] <Heat Treatment>

[0199] The cold-rolled steel sheet obtained by cold rolling is subjected to heat treatment under the conditions described below.

[0200] In summary, a cold-rolled steel sheet is maintained (heated) at temperature range T1, then cooled to a cooling stop temperature T2, and then maintained (reheated) at temperature range T2.

[0201] Temperature Range T1 : 800 ∼ 950 ℃

[0202] When the temperature of the temperature range T1 is excessively low, the two-phase region is maintained, so the total area ratio of tempered martensite and bainite in the final microstructure is reduced.

[0203] For this reason, the temperature of the temperature range T1 is 800 ℃ or higher, preferably 820 ℃ or higher, and more preferably 840 ℃ or higher.

[0204] Meanwhile, if the temperature in the temperature range T1 is excessively high, the austenite grain size increases, and the orientation of the iron-based carbides precipitated during the subsequent temperature range T3 becomes uneven, and the ratio (p) becomes too low, so the resistance to delayed fracture deteriorates.

[0205] For this reason, it is 950 ℃ or lower, 940 ℃ or lower is preferable, and 920 ℃ or lower is more preferable.

[0206] 《Hold time at temperature range T1: 30 seconds or more》

[0207] If the holding time in the temperature range T1 is excessively short, sufficient recrystallization is not carried out. In addition, the formation of austenite becomes insufficient, and the total area ratio of tempered martensite and bainite in the finally obtained microstructure becomes insufficient.

[0208] For this reason, the holding time in temperature range T1 is 30 seconds or more, preferably 65 seconds or more, and more preferably 100 seconds or more.

[0209] The upper limit of the holding time in temperature range T1 is not specifically limited, for example, 800 seconds, 500 seconds is preferred, and 200 seconds is more preferred.

[0210] Cooling Stop Temperature T2: 250°C or lower

[0211] If the cooling stop temperature T2 is excessively high, a large amount of residual austenite remains when cooling is stopped, and the area ratio of fresh martensite in the microstructure obtained at the end becomes excessive.

[0212] For this reason, the cooling stop temperature T2 is 250 ℃ or lower, preferably 240 ℃ or lower, and more preferably 230 ℃ or lower.

[0213] The lower limit of the cooling stop temperature T2 is not particularly limited, but, for example, 100°C, and 120°C is preferred.

[0214] "cooling"

[0215] In cooling from temperature range T1 to cooling stop temperature T2, under conditions satisfying Equations 1 and 2 below, first cooling is performed to temperature T at an average cooling rate R1 of 10.0 to 50.0 °C / s, and then second cooling is performed to cooling stop temperature T2 at an average cooling rate R2.

[0216] Equation 1 : 0.10 < (R2 / R1) < 0.70

[0217] Equation 2: (21.52×T+5630)×R2 -0.022 ≥ 12200

[0218] The average cooling rate R2 of the second cooling is determined by the average cooling rate R1 of the first cooling and the end temperature (temperature T) of the first cooling.

[0219] (Equation 1)

[0220] As shown in Equation 1 above, the average cooling rate R2 of the second cooling is made gentler than the average cooling rate R1 of the first cooling. The reason for this is to promote the nucleation of iron carbides during the second cooling, thereby allowing fine iron carbides to be widely present in the microstructure obtained at the end.

[0221] That is, by ensuring that (R2 / R1) in the above Equation 1 is less than 0.70, the value of the ratio (p) is prevented from becoming too small.

[0222] (Equation 2)

[0223] By satisfying the above Equation 2, proper nucleation of iron carbides is promoted, so the formation of iron carbides with an excessive average aspect ratio is suppressed during maintenance (reheating) in the temperature range T3 described later.

[0224] In addition, by satisfying the above Equation 2, nucleation of iron carbides occurs during secondary cooling, and the ratio (p) in the microstructure obtained at the end is suppressed.

[0225] For this reason, the value of the left side of the above Equation 2 is 12200 or more, 12250 or more is more preferable, and 12290 or more is even more preferable.

[0226] The upper limit is not specifically limited, but the value of the left side of Equation 2 above is preferably 14500 or less, more preferably 14250 or less, and even more preferably 14200 or less.

[0227] Equation 2 above is derived from the result of calculating the tempering parameter in the case where temperature fluctuation occurs.

[0228] According to Non-Patent Literature 1, when calculating tempering parameters in the case where temperature fluctuation occurs, it is necessary to convert the entire process of heat treatment into tempering that is equivalent to maintaining a certain temperature for a certain period of time.

[0229] · Non-patent Literature 1: Toshihiro Tsuchiyama, "Interpretation of the Physical Meaning of Tempering Parameters and Application to Continuous Heating and Cooling Heat Treatment Processes," Heat Treatment, Japan Heat Treatment Technology Association, June 2002, Vol. 42, No. 3, pp. 163-168

[0230] The time from the start temperature of secondary cooling to the cooling stop temperature is divided, for example, by Δt, and the initial temperatures of each interval obtained from the average cooling rate are T1, T2, T3, … T n ...is set as follows. When the tempering parameter at the time Δt elapsed from the start of cooling is T1×(log(Δt)+20), the equivalent time Δt' for performing tempering equivalent to this value at the next interval temperature T2 is,

[0231] T1×(log(Δt)+20) = T2×(log(Δt')+20)

[0232] And, if we calculate the tampering parameter from the 1st to the end of the 2nd interval,

[0233] T2×(log(Δt'+Δt)+20)

[0234] It becomes.

[0235] Here, t2 = Let Δt' + Δt, and perform this operation up to the n-th interval. If tempering by secondary cooling is converted into tempering maintained at the cooling stop temperature, the equivalent constant temperature holding time t n silver,

[0236] log(t n ) = (Tn-1 / T n )×((logt n-1 +20)-20)

[0237] This becomes. This equivalent constant temperature holding time t n and the stop temperature T of secondary cooling sq By using and the following equation, the tempering parameters for continuous cooling can be calculated.

[0238] T sq ×(log(t n )+20)

[0239] Various cooling stop temperatures T in this equation sq and equivalent constant temperature holding time t n By substituting the values ​​to obtain an approximation formula and taking into account the minimum value of the tempering parameter that obtains the desired microstructure, the above Equation 2 is obtained.

[0240] Temperature Range T3: 250–400 ℃

[0241] If the temperature of temperature range T3 is excessively low, growth of iron carbides by tempering does not occur, and the ratio (p) becomes too low, resulting in inferior resistance to delayed fracture.

[0242] For this reason, the temperature of temperature range T3 is 250 ℃ or higher, preferably 260 ℃ or higher, and more preferably 270 ℃ or higher.

[0243] Meanwhile, if the temperature in temperature range T3 is excessively high, iron carbides in tempered martensite and bainite coarsen, and the average radius of the iron carbides becomes excessive, making it easy for initial cracks to form in the shear section, and the hole expansion ability of the steel plate deteriorates.

[0244] For this reason, the temperature of temperature range T3 is 400 ℃ or lower, preferably 380 ℃ or lower, and more preferably 360 ℃ or lower.

[0245] Heating rate to temperature range T3: 6.0 to 14.0 ℃ / s

[0246] If the heating rate up to temperature range T3 is excessively low, iron carbides in tempered martensite and bainite coarsen, and the average radius of the iron carbides becomes excessive, making it easy for initial cracks to form in the shear section, and the hole expansion ability of the steel plate deteriorates.

[0247] For this reason, the heating rate up to temperature range T3 is 6.0 ℃ / s or higher, preferably 6.5 ℃ / s or higher, and more preferably 7.0 ℃ / s or higher.

[0248] On the other hand, if the heating rate up to temperature range T3 is excessively high, the growth of iron carbides due to tempering does not occur, and the ratio (p) becomes too low, resulting in inferior resistance to delayed fracture.

[0249] For this reason, the heating rate up to temperature range T3 is 14.0 ℃ / s or less, preferably 13.0 ℃ / s or less, and more preferably 12.0 ℃ / s or less.

[0250] 《Hold time at temperature range T3: 30 seconds or more》

[0251] If the holding time in the temperature range T3 is excessively short, the area ratio of fresh martensite in the final microstructure becomes excessive.

[0252] For this reason, the holding time in temperature range T3 is 30 seconds or more, preferably 100 seconds or more, and more preferably 180 seconds or more.

[0253] The upper limit of the holding time in temperature range T3 is not specifically limited, for example, 800 seconds, 500 seconds is preferred, and 300 seconds is more preferred.

[0254] <Plating Treatment>

[0255] For the cold-rolled steel sheet subjected to the heat treatment described above, a plating treatment to form a plating layer may be performed. Examples of plating treatments include hot-dip galvanizing. In this case, a zinc plating layer is formed as the plating layer.

[0256] When performing hot-dip galvanizing treatment, for example, a cold-rolled steel sheet that has undergone the heat treatment described above is immersed in a hot-dip galvanizing bath at 440 to 500°C. After immersion, the amount of the plating layer adhered is adjusted by gas wiping, etc.

[0257] The molten zinc plating bath may contain elements such as Al, Mg, and Si, and may also contain elements such as Pb, Sb, Fe, Mg, Mn, Ni, Ca, Ti, V, Cr, Co, and Sn. The amount of Al in the molten zinc plating bath is preferably 0.08 to 0.30%.

[0258] The plating treatment may include an alloying treatment that alloys the formed plating layer.

[0259] When performing an alloying treatment after hot-dip galvanizing, the zinc plating layer is alloyed at a temperature of 450 to 600°C (alloying temperature). If the alloying temperature is excessively high, the untransformed austenite transforms into pearlite, and the area percentage of the retained austenite becomes insufficient.

[0260] The Fe concentration of the alloyed zinc plating layer is preferably 8 to 17 mass%.

[0261] In the case where plating treatment is performed, the cold-rolled steel sheet subjected to heat treatment and plating treatment corresponds to the high-strength steel sheet of the present invention.

[0262] Meanwhile, in cases where plating treatment is not performed, a heat-treated cold-rolled steel sheet corresponds to the high-strength steel sheet of the present invention.

[0263] Examples

[0264] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples described below.

[0265] <Manufacture of Steel Plates>

[0266] Molten steel having the composition shown in Table 1 below, with the remainder being Fe and unavoidable impurities, was produced in a converter, and a steel slab was obtained by a continuous casting method.

[0267] For the obtained steel slab, hot rolling, coiling, cold rolling, and heat treatment were performed under the conditions shown in Table 2 below to obtain a cold-rolled steel sheet (CR) with a thickness of 1.4 mm. The reduction rate for cold rolling was set to 50%.

[0268] For several cold-rolled steel sheets, a galvanized layer was formed on both sides by performing a hot-dip galvanizing treatment to obtain hot-dip galvanized steel sheets (GI). The amount of the galvanized layer (amount per side) was 45 g / m² 2 ...did so.

[0269] In addition, for several hot-dip galvanized steel sheets (GI), the zinc plating layer formed by performing an alloying treatment was alloyed to obtain an alloyed hot-dip galvanized steel sheet (GA). In the alloying treatment, the Fe concentration of the alloyed zinc plating layer was adjusted to be within the range of 9 to 12 mass%.

[0270] For the hot-dip galvanized steel sheet (GI), a hot-dip galvanizing bath with an Al content of 0.19 mass% was used. For the hot-dip galvanized steel sheet (GA), a hot-dip galvanizing bath with an Al content of 0.14 mass% was used. The bath temperature was set to 465 ℃ for all.

[0271] Hereinafter, for convenience, cold-rolled steel sheets (CR), hot-dip galvanized steel sheets (GI), and alloyed hot-dip galvanized steel sheets (GA) are all simply referred to as "steel sheets."

[0272] In the “Type” column of Table 2 below, “CR,” “GI,” and “GA” are indicated depending on the obtained steel plate.

[0273] <Observation of Microstructure>

[0274] The obtained steel plate was polished so that the cross-section (L cross-section) at the 1 / 4 position of the plate thickness parallel to the rolling direction (a position corresponding to 1 / 4 of the plate thickness in the depth direction from the surface of the steel plate) became the observation surface, and an observation sample was prepared.

[0275] Using the prepared observation samples, the microstructure was observed as follows, and the area ratio of each tissue was calculated. The results are shown in Table 3 below.

[0276] In Table 3 below, tempered martensite is denoted as “TM”, bainite as “B”, and fresh martensite as “FM”.

[0277] Area ratio of tempered martensite, bainite, and fresh martensite

[0278] After etching the observation surface of the observation sample using Nital, 10 fields of view were observed at a magnification of 2000x using a scanning electron microscope (SEM) to obtain SEM images.

[0279] For the obtained SEM images, the area percentage (unit: %) of each tissue was calculated. The average area percentage of 10 fields of view was taken as the area percentage of each tissue.

[0280] In the SEM image, the light gray area was determined to be fresh martensite, and the dark gray area where carbides were precipitated was determined to be tempered martensite and bainite.

[0281] Since fresh martensite and retained austenite cannot be clearly distinguished in SEM images, the area ratio of fresh martensite was set as the value obtained by subtracting the area ratio of retained austenite obtained by the method described below from the area ratio of the light gray region.

[0282] Average radius of origin and average aspect ratio of iron carbides

[0283] After etching the observation surface of the observation sample using Nital, 10 fields of view were observed at a magnification of 5000x using a scanning electron microscope (SEM) to obtain SEM images.

[0284] For the obtained SEM images, the major axis a and minor axis b of each iron-based carbide present in tempered martensite and bainite were measured.

[0285] The equivalent radius (unit: μm) of each iron carbide was calculated from the formula √(a×b) / 2. In addition, the aspect ratio (a / b) of each iron carbide was calculated.

[0286] The average values ​​of the radius of origin and aspect ratio of the 10-point field of view were taken as the average radius of origin and average aspect ratio of the iron carbide, respectively.

[0287] Ratio (p)

[0288] After etching the observation surface of the observation sample using Nital, three fields of view were observed at a magnification of 5000x using a scanning electron microscope (SEM) to obtain SEM images.

[0289] For the obtained SEM image, the area SA1 occupied by the particles of tempered martensite and bainite was measured.

[0290] Subsequently, 7 to 35 iron carbides / ㎛ with the major axis oriented in the same direction within the range of 0 to 10° 2 The area SA2 occupied by particles (tempered martensite and bainite) containing the number density was measured.

[0291] After that, the ratio (p) of area SA2 to area SA1 (unit: %) was calculated.

[0292] At this time, among the iron carbides present in the particles, iron carbides whose long axis direction is within 10° to the right or left were determined to be “iron carbides whose long axis direction is oriented in the same direction within the range of 0 to 10°”.

[0293] <Measurement of diffusible hydrogen content in steel>

[0294] A test specimen of size 5 mm × 30 mm was cut from the obtained steel plate. If a plating layer (zinc plating layer or alloyed zinc plating layer) was formed, the plating layer was removed using a router (precision grinder).

[0295] The test specimen was placed inside a quartz tube, and the inside of the quartz tube was replaced with argon gas (Ar). After that, the inside of the quartz tube was heated to 400 ℃ at a rate of 200 ℃ / hr, and the amount of hydrogen generated from the inside of the quartz tube during the heating was measured by a heating analysis method using a gas chromatograph.

[0296] The cumulative value of the amount of hydrogen detected in the temperature range from room temperature (25 ℃) to less than 250 ℃ was calculated as the amount of diffusible hydrogen in steel (unit: mass%). The results are shown in Table 3 below.

[0297] <Evaluation>

[0298] The obtained steel plates were evaluated by the following tests. The results are shown in Table 3 below.

[0299] 《Tensile Test》

[0300] From the obtained steel plate, a JIS No. 5 test specimen was taken with the direction perpendicular to the rolling direction as the tensile direction. Using the taken test specimen, a tensile test was performed in accordance with JIS Z 2241 (2011) and the tensile strength (TS) was measured.

[0301] If TS is 1320 MPa or higher, it was evaluated as high strength.

[0302] Hole Expansion Test

[0303] For the obtained steel plate, a hole expansion test was performed in accordance with JIS Z 2256 (2010).

[0304] Specifically, the obtained steel plate was cut to obtain a test specimen of 100 mm × 100 mm size. A hole with a diameter of 10 mm was punched in the obtained test specimen with a clearance of 12 ± 1 %. Subsequently, using a die with an inner diameter of 75 mm, a conical punch with an apex angle of 60° was inserted into the hole while applying a creasing force of 9 ton, and the hole diameter D at the crack initiation limit f [mm] was measured. The initial hole diameter was set to D0 (unit: mm), and the hole expansion rate λ (unit: %) was calculated from the following formula. If λ was 35% or more, the hole expandability was evaluated as excellent.

[0305] λ = {(D f -D0) / D0} × 100

[0306] Evaluation Test for Delayed Fracture Characteristics

[0307] Test specimens were taken from the obtained steel plate. If a plating layer was formed, it was dissolved and removed using diluted hydrochloric acid, and after storing at room temperature for 1 day (dehydrogenation treatment), test specimens were taken.

[0308] The size of the test specimen was set so that the length of the long side (length in the direction perpendicular to rolling) was 100 mm and the length of the short side (length in the rolling direction) was 30 mm.

[0309] In the test specimen, the cross-section on the long side was designated as the evaluation cross-section, and the cross-section on the short side was designated as the non-evaluation cross-section.

[0310] The cutting of the evaluation cross-section was performed by shearing. The clearance for shearing was 10%, and the rake angle was 0.5 degrees. The evaluation cross-section was left in the sheared state; that is, no machining was performed to remove the burrs. On the other hand, for the non-evaluation cross-section, machining was performed to remove the burrs.

[0311] Bending was performed on these test specimens. The bending was performed under conditions where the ratio of the bending radius R to the plate thickness t of the test specimen (R / t) was 4.0 and the bending angle was 90 degrees (V-bending).

[0312] For example, when the plate thickness t is 2.0 mm, a punch with a tip radius of 8.0 mm was used. More specifically, a punch having the tip radius described above and also having a U-shape (the tip part is semicircular and the thickness of the body part is 2R) was used.

[0313] In addition, for the bending process, a die with a corner bending radius of 30 mm was used.

[0314] In the bending process, a bending portion with a bending angle of 90 degrees was formed on the test specimen by adjusting the depth to which the punch pushes the test specimen.

[0315] A test specimen with a formed bending section was placed between and tightened using a hydraulic jack, and bolted while the following residual stresses S1, S2, or S3 were applied to the outermost layer of the bending section.

[0316] · Residual stress S1: Residual stress between 1300 MPa and 1500 MPa

[0317] · Residual stress S2: Residual stress exceeding 1500 MPa and not exceeding 1700 MPa

[0318] · Residual stress S3: Residual stress exceeding 1,700 MPa and not exceeding 1,900 MPa

[0319] For each applied residual stress S1, S2, and S3, the number of test specimens was set to 2.

[0320] The required tightening amount was calculated by CAE (Computer Aided Engineering) analysis.

[0321] Bolt tightening was performed by passing the bolt through an elliptical hole (short axis: 10 mm, long axis: 15 mm) formed 10 mm inward from the non-standard cross-section of the test specimen.

[0322] The test specimens after bolt tightening were immersed in hydrochloric acid (aqueous hydrogen chloride solution) with a pH of 4, and the pH was maintained constant at 25°C. The amount of hydrochloric acid was set to at least 1 L per test specimen.

[0323] After 48 hours had elapsed following immersion, the presence or absence of microcracks visible to the naked eye (having a length of approximately 1 mm) was checked on the test specimens in hydrochloric acid. These microcracks indicate the initial state of delayed fracture.

[0324] The results based on the presence or absence of microcracks ("×", "△", "○", or "◎" shown below) are listed in Table 3 below.

[0325] × : In the test specimen subjected to residual stress S1, one or more microcracks were identified.

[0326] △ : In the specimen with residual stress S1, no microcracks were detected, but in the specimen with residual stress S2, one or more microcracks were detected.

[0327] ○ : In the test specimens loaded with residual stress S1 and residual stress S2, no microcracks were detected, but in the test specimen loaded with residual stress S3, one or more microcracks were detected.

[0328] ◎ : No microcracks were detected in any of the test specimens.

[0329] If it is "△", "○", or "◎", the delayed breakdown characteristics were evaluated as excellent.

[0330] "○" or "◎" is preferable because it has superior delayed fracture resistance, and "◎" is more preferable because it has even superior delayed fracture resistance.

[0331] The lines in Tables 1 to 3 below indicate areas outside the scope of the present invention.

[0332]

[0333]

[0334]

[0335] <Summary of Evaluation Results>

[0336] As shown in Table 3 above, the steel plates 1, 3, 5 to 6, 9 to 12, 15, 19 to 21, 24 to 26, 29 to 30, and 34 had at least one of the tensile strength, ductility, hole expansion, and delayed fracture resistance characteristics insufficient.

[0337] In this regard, it was found that the steel plates 2, 4, 7 to 8, 13 to 14, 16 to 18, 22 to 23, 27 to 28, 31 to 33, and 35 to 39 all had a tensile strength of 1320 MPa or higher, and also had excellent hole expansion and delayed fracture resistance characteristics.

[0338] For these steel plates, the evaluation results of the delayed fracture characteristics showed that steel plates with a ratio (p) of 26% or more (less than 28%) were rated "△", steel plates with a ratio (p) of 29% or more (less than 38%) were rated "○", and steel plates with a ratio (p) of 39% or more were rated "◎".

Claims

Claim 1 A steel having a composition in mass% containing C: 0.130–0.350%, Si: 0.50–2.50%, Mn: 2.00–4.00%, P: 0.100% or less, S: 0.0500% or less, Al: 0.001–2.000%, and N: 0.0100% or less, with the remainder being Fe and unavoidable impurities, and having a microstructure, wherein the diffusible hydrogen content in the steel is 0.50 mass ppm or less, and in the microstructure, the total area percentage of tempered martensite and bainite is 70.0% or more, and the area percentage of fresh martensite is 15.0% or less, and the iron-based carbides present in the tempered martensite and bainite have an average equivalent radius of 0.10 μm or less, and an average The aspect ratio is 4.5 or less, and among the tempered martensite and bainite, 7 to 35 iron-based carbides / ㎛ in which the direction of the major axis is oriented in the same direction within the range of 0 to 10° 2 A high-strength steel plate having a ratio (p) of tempered martensite and bainite containing as a number density of 25 to 70%. Claim 2 In claim 1, the above component composition further comprises, in mass%, Ti: 0.100% or less, Nb: 0.100% or less, V: 0.500% or less, W: 0.500% or less, B: 0.0100% or less, Ni: 2.000% or less, Co: 2.000% or less, Cr: 1.000% or less, Mo: 1.000% or less, Cu: 1.000% or less, Sn: 0.500% or less, Sb: 0.500% or less, Ta: 0.100% or less, Zr: 0.200% or less, Hf: 0.020% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, and REM: 0.0100 High-strength steel plate containing at least one element selected from the group consisting of % or less. Claim 3 A high-strength steel sheet having a plating layer on its surface, according to claim 1 or 2. Claim 4 A high-strength steel sheet according to claim 3, wherein the plating layer is an alloyed plating layer. Claim 5 A method for manufacturing a high-strength steel sheet as described in claim 1 or 2, wherein a steel slab having the compositional component described in claim 1 or 2 is heated to 1100°C or higher and hot-rolled at a finishing rolling end temperature of 850 to 950°C to obtain a hot-rolled steel sheet, the hot-rolled steel sheet is coiled at a coiling temperature of 700°C or lower and subsequently cold-rolled to obtain a cold-rolled steel sheet, and heat treatment is performed on the cold-rolled steel sheet, wherein in the heat treatment, the cold-rolled steel sheet is maintained at a temperature range T1 of 800 to 950°C for 30 seconds or more, and subsequently cooled to a cooling stop temperature T2 of 250°C or lower, and subsequently heated to a temperature range T3 of 250 to 400°C at a heating rate of 6.0 to 14.0°C / s and maintained for 30 seconds or more, and in the cooling, the cold-rolled A method for manufacturing a high-strength steel plate, wherein the steel plate is first cooled to a temperature T at an average cooling rate R1 of 10.0 to 50.0 ℃ / s under conditions satisfying the following Equations 1 and 2, and subsequently secondarily cooled to a cooling stop temperature T2 at an average cooling rate R2. Equation 1: 0.10 < (R2 / R1) < 0.70 Equation 2: (21.52×T+5630)×R2 -0.022 ≥ 12200 Claim 6 A method for manufacturing a high-strength steel sheet according to claim 5, wherein, after the heat treatment, a plating treatment is performed to form a plating layer on the cold-rolled steel sheet. Claim 7 A method for manufacturing a high-strength steel sheet according to claim 6, wherein the plating treatment comprises an alloying plating treatment that alloys the plating layer.

Citation Information

Patent Citations

  • Ultrahigh strength cold rolled steel sheet excellent in hydrogen embrittlement resistance and manufacturing method therefor

    JP2016050343A

  • High strength steel sheet and method for producing the same

    JP2021123801A

  • Steel sheet

    WO2018055695A1

  • Hot rolled steel sheet and production method thereof

    WO2020179387A1

  • High-strength steel sheet and method for manufacturing same

    WO2021019947A1